Separating the hawks from the doves: Evidence from continuous time laboratory games - Ryan Oprea; Keith Henwood; Daniel Friedman (University of California, Economics Department, 2010)
Human players in our laboratory experiment received flow payoffs over 120 seconds each period from a standard Hawk-Dove bimatrix game played in continuous time. Play converged closely to the symmetric mixed Nash equilibrium under a one-population matching protocol. When the same players were matched in a two-population protocol with the same bimatrix, they showed clear movement towards an asymmetric (and very inequitable) pure Nash equilibrium of the game. These findings support distinctive predictions of evolutionary game theory.
Keywords: C73; C92; D74; 330; Evolutionary dynamics; Hawk-Dove game; game theory; laboratory experiment; continuous time game